The comparison of surface hardness between thermoplastic nylon resin and heat-cured acrylic resin - Utami, Marina; Febrida, Renny; Djustiana, Nina (Universitas Padjadjaran, 2009)
The surface hardness level of a denture base material is related to the resistance to abrasion, scratch, polishing and water sorption. Nowadays, thermoplastic nylon resins and heat-cured acrylic resins are used as denture base materials. Denture base must be immersed in water to maintain its humidity. The objective of this research was to compare the surface hardness level between thermoplastic nylon resins and heat-cured acrylic resins. Materials used for the research were thermoplastic nylon resins from Valplast and heat-cured acrylic resins QC-20, with a sample size of 64x(10±0.03)x(2.5±0.03) mm. Surface hardness is measured with Vickers Microhardness Tester and the data were analyzed by ANOVA method. The results showed that comparison ratio of surface hardness level between thermoplastic nylon resins and heat-cured acrylic resins before immersion is 3.2:7.3 VHN respectively, while the comparison value of both resins after immersion is 2.8:6.6 VHN. In conclusion, the surface hardness level of thermoplastic nylon resins is lower compared to heat-cured acrylic resins. This result is due to thermoplastic nylon resin’s higher porosity, its different polymer chains, and the plasticizers effect after immersion in water.